A Post-style proof of completeness theorem for symmetric relatedness Logic S - Klonowski, Mateusz (Bulletin of the Section of Logic, 2018)
One of the logic defined by Richard Epstein in a context of an analysis of subject matter relationship is Symmetric Relatedness Logic S. In the monograph [2] we can find some open problems concerning relatedness logic, a Post-style completeness theorem for logic S is one of them. Our paper introduces a solution of this metalogical issue.